Mechanisms influencing retrograde flow in the atrioventricular canal during early embryonic cardiogenesis. Issue 14 (3rd October 2016) - Bulk, Alexander; Bark, David; Johnson, Brennan; Garrity, Deborah; Dasi, Lakshmi Prasad
Abstract: Normal development of the heart is regulated, in part, by mechanical influences associated with blood flow during early stages of embryogenesis. Specifically, the potential for retrograde flow at the atrioventricular canal (AVC) is particularly important in valve development. However, the mechanisms causing this retrograde flow have received little attention. In this study, a numerical analysis was performed on images of the embryonic zebrafish heart between 48 and 55 hpf. During these stages, normal retrograde flow is prevalent. To manipulate this flow, zebrafish were placed in a centrifuge and subjected to a hypergravity environment to alter the cardiac preload at various six-hour intervals between 24 and 48 hpf. Parameters of the pumping mechanics were then analyzed through a spatiotemporal analysis of processed image sequences. We find that the loss of retrograde flow in experimentally manipulated embryos occurs in part because of a greater resistance in the form of atrial and AVC contractile closure. Additionally, during retrograde flow, these embryos exhibit significantly greater pressure difference across the AVC based on calculations of expansive and contractile rates of the atrium and ventricle. These results elucidated that the developing heart is highly sensitive to small changes in pumping mechanics as it strives to maintain normal hemodynamic conditions necessary for later cardiac development.